To solve the quadratic equation \( 3(x^2 + 1) - 5 = 7 \), we will first simplify the equation step by step.
-
Start with the original equation: \[ 3(x^2 + 1) - 5 = 7 \]
-
Distribute the 3: \[ 3x^2 + 3 - 5 = 7 \]
-
Combine like terms: \[ 3x^2 - 2 = 7 \]
-
Add 2 to both sides of the equation: \[ 3x^2 = 9 \]
-
Divide both sides by 3: \[ x^2 = 3 \]
-
Take the square root of both sides: \[ x = \pm \sqrt{3} \]
So, the solutions to the equation are: \[ x = \sqrt{3} \quad \text{and} \quad x = -\sqrt{3} \]